2013
DOI: 10.1136/bcr-2013-200573
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic hepatitis and acute liver failure in a patient with newly onset atrial fibrillation and diltiazem infusion

Abstract: SUMMARYHypoxic hepatitis (HH) most commonly results from haemodynamic instability and disruption of hepatic flow. The vast majority of cases are caused by cardiac failure, respiratory failure and septic shock. We report a case of HH, acute liver failure, acute kidney failure and progressive thrombocytopenia that developed following a hypotensive episode in a patient treated with intravenous diltiazem for a newly developed atrial fibrillation (A-fib). The pre-existing liver diseases, including chronic alcohol u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Health services research that informs health care policy, planning and provision was also identified as a key area for future research in the PRISMA workshop [ 9 ]. It is interesting to note that a UK focused consultation for palliative care research demonstrated a greater emphasis on health economic aspects and service delivery [ 31 ]. A rationale for this may be the greater involvement of service funders and providers in the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Health services research that informs health care policy, planning and provision was also identified as a key area for future research in the PRISMA workshop [ 9 ]. It is interesting to note that a UK focused consultation for palliative care research demonstrated a greater emphasis on health economic aspects and service delivery [ 31 ]. A rationale for this may be the greater involvement of service funders and providers in the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Liver congestion due to heart failure can also be a contributing factor. In this case of hypoxic hepatitis, the diltiazem infusion was stopped; anticoagulation was held initially because of liver toxicity-induced coagulopathy [ 48 ].…”
Section: Reviewmentioning
confidence: 99%
“…Cardiohepatic interaction has been noted in patients with heart failure [5], atrial fibrillation [6], and myocardial infarction [7]. Although the relationship between aminotransferase levels and cardiovascular disease has become a matter of discussion [8, 9], the prognostic utility of aminotransferase has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%